2015
DOI: 10.1021/acs.est.5b01116
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Fate of Silver Nanoparticles in Boreal Lake Ecosystems

Abstract: Silver nanoparticles (AgNPs) are currently the most commonly used nanoparticles in consumer products, yet their environmental fate in natural waters is poorly understood. In the present study, we investigated the persistence, transformations and distribution of polyvinylpyrrolidone (PVP) and citrate (CT) coated AgNPs in boreal lake mesocosms dosed either with a 6-week chronic regimen or a one-time pulse treatment at environmentally relevant dosing levels. In the chronic treatments, total Ag (TAg) concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 51 publications
(151 reference statements)
1
48
0
Order By: Relevance
“…In the 386 two mesocosms in which CNIS were deployed, the concentrations of total silver (TAg) steadily 387 increased over the course of the study as CT-AgNPs and PVP-AgNPs were added and reached 388 final concentrations that were approximately 60% of the predicted nominal concentration (Figure 389 3). Deviation from the estimated nominal concentration might be explained by losses in the water 390 column through sedimentation and adsorption to the mesocosm walls, as discussed previously by 391 Furtado et al (2015). The estimated TWA concentrations for silver measured in the TAg and the colloidal Ag 398 (i.e.…”
Section: Field Deployment Of Cnis-chemcatcher ® 382mentioning
confidence: 79%
See 4 more Smart Citations
“…In the 386 two mesocosms in which CNIS were deployed, the concentrations of total silver (TAg) steadily 387 increased over the course of the study as CT-AgNPs and PVP-AgNPs were added and reached 388 final concentrations that were approximately 60% of the predicted nominal concentration (Figure 389 3). Deviation from the estimated nominal concentration might be explained by losses in the water 390 column through sedimentation and adsorption to the mesocosm walls, as discussed previously by 391 Furtado et al (2015). The estimated TWA concentrations for silver measured in the TAg and the colloidal Ag 398 (i.e.…”
Section: Field Deployment Of Cnis-chemcatcher ® 382mentioning
confidence: 79%
“…Water samples were collected over the 52 day mesocosm 385 study and three size fractions were analyzed, as previously reported by Furtado et al (2015). In the 386 two mesocosms in which CNIS were deployed, the concentrations of total silver (TAg) steadily 387 increased over the course of the study as CT-AgNPs and PVP-AgNPs were added and reached 388 final concentrations that were approximately 60% of the predicted nominal concentration (Figure 389 3).…”
Section: Field Deployment Of Cnis-chemcatcher ® 382mentioning
confidence: 90%
See 3 more Smart Citations